2018
DOI: 10.4236/ajac.2018.99033
|View full text |Cite
|
Sign up to set email alerts
|

Application of Desert Date (<i>Balanites aegyptiaca</i>) Seed Oil as Potential Raw Material in the Formulation of Soap and Lotion

Abstract: Balanites aegyptiaca has multiplicity of uses and almost every part of the plant is useful including its flowers, leaves, bark, root and fruit. In this study, oil from Desert date (Balanites aegyptiaca) kernel seed was extracted, analyzed and used in the formulation of soap and lotion. The physical parameters determined were oil content, specific gravity, refractive index and moisture content. These were found to be 45.32% ± 0.0026%, 0.90 ± 0.03, 1.45% and 0.114% ± 0.04%, respectively. The chemical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
4
5
0
Order By: Relevance
“…The implications of these findings were further discussed. The oil yield obtained was 45.62% which was similar to findings by Ogala et al (2018) and Zang et al (2018) who reported yields of range 35 % to 46 %. Also, Chapagain and Wiesman (2011) reported that the general yield of B. aegyptiaca range from 30 % to 50 % regardless of the extraction method used.…”
Section: Resultssupporting
confidence: 90%
“…The implications of these findings were further discussed. The oil yield obtained was 45.62% which was similar to findings by Ogala et al (2018) and Zang et al (2018) who reported yields of range 35 % to 46 %. Also, Chapagain and Wiesman (2011) reported that the general yield of B. aegyptiaca range from 30 % to 50 % regardless of the extraction method used.…”
Section: Resultssupporting
confidence: 90%
“…51 The moisture content and density were 0.491% and 0.9083 g/cm 3 , respectively. The low moisture content indicates the stability of oil reducing microbial activities 52 as well as reduced soap formation tendency as the presence of water inhibits transesterification. 53 The lower density shows the presence of low molecular weight fatty acids.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Oil has been extracted from B. aegyptiaca seed giving different yields when different extraction techniques are used, for instance, Ogala et al (2018) reported a yield of 36.5 % when Soxhlet extraction technique is used and when n-hexane is the extraction solvent. Zang et al (2018) on the other hand reported a yield of 45.32 % when a mixture of mechanical and Soxhlet extraction methods were used. However, Chapagain and Wiesman (2011) reported that the general yield of oil from B. aegyptiaca ranged from 30 % to 50 % regardless of the extraction method used.…”
mentioning
confidence: 99%